2020
DOI: 10.46328/ijonse.30
|View full text |Cite
|
Sign up to set email alerts
|

The Reconstruction Model of Science Learning based PhET-Problem Solving

Abstract: This study investigates the effects of science learning model reconstruction based on student needs, in order to generate more operational standards and teaching materials. The conceptual understanding through virtual laboratory appears minimal, based on the analysis addressing the demands of junior high school students in several locations in Papua. Hence, there is a necessity to reform the learning structure through the utilization of physics education technology (PhET). Furthermore, the model was reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…This has been done for a long time by developed countries (such as England, Germany, France, the United States and other countries), they continue to develop interactive learning media [34], [35]. Previous studies reported that technological developments in learning require educators to develop more effective and efficient learning media [36]. Other studies also report that online instructional formats such as e-modules and computer-based simulation programs can enhance knowledge [37]- [39],skills [40], [41],and promote opportunities flexible learning at a low cost [42].…”
Section: Discussionmentioning
confidence: 99%
“…This has been done for a long time by developed countries (such as England, Germany, France, the United States and other countries), they continue to develop interactive learning media [34], [35]. Previous studies reported that technological developments in learning require educators to develop more effective and efficient learning media [36]. Other studies also report that online instructional formats such as e-modules and computer-based simulation programs can enhance knowledge [37]- [39],skills [40], [41],and promote opportunities flexible learning at a low cost [42].…”
Section: Discussionmentioning
confidence: 99%
“…The simulations provide a user-friendly platform for data collection, visualization, and analysis, making the learning experience more interactive and meaningful. PhET simulations offer students a virtual environment that enables them to engage in hands-on experimentation, explore complex scientific concepts and understand it (Doloksaribu & Triwiyono, 2020). Students who used the simulations as part of their coursework showed greater improvements in their ability to solve complex problems and apply theoretical concepts to real-world situations.…”
Section: Description Of Problem Solving Skillsmentioning
confidence: 99%
“…Gambar 1. Penggabungan PhET Problem Solving (Doloksaribu, F., 2020) Berdasarkan permasalahan terbatasnya internet, pemanfaatan fasilitas laboratorium di sekolah-sekolah Papua, rendahnya minat siswa dalam pelajaran IPA, serta pentingnya IPA dalam melatih siswa mencari solusi dalam permasalahan, maka peneliti mencari alternatif solusi guna meningkatkan kemampuan siswa dalam memahami konsep IPA. Rekonstruksi materi ajar dengan PhET berbasis problem solving dibuat untuk mempermudah siswa memahami konsep melalui operasi simulasi.…”
Section: Konstruksi Model Pembelajaran Ipa Berbasis Physics Eduction Technologyunclassified